Isolated ulnopalmar dislocation of 5th carpometacarpal joint: a rare case report - P., Pratheeksh; Japatti, Manjunath S.; Thimmegowda, Ranganatha B.; K., Rakshith Kumar (International Journal of Research in Orthopaedics, 2021)
Isolated volar dislocations of the fifth carpometacarpal joints are an uncommon injury. They are classified as ulnopalmar or radiopalmar dislocations. It can be easily missed on standard radiographs. A high degree of suspicion and accurate reduction is pivotal in restoring the functional outcome of the hand. In our case report, a forty year old man presented with ulnopalmar dislocation of the fifth carpometacarpal joint and was treated with open reduction and K wiring. We review the literature and discuss the available methods of management.